Establishing a Dual Murine Model to Explore the Interactions Between Diabetes and Periodontitis in Mice - Silva, Bárbara R.; Hidalgo, Marco A. R.; Silva, Renata C. L.; de Avila, Erica D.; Fuentes, Deivys L. P.; Carlos, Iracilda Z.; Figueiredo, Ingrid D.; Cerri, Estela S.; Cerri, Paulo S.; Baviera, Amanda M.; de Molon, Rafael Scaf; Scarel-Caminaga, Raquel M. (International journal of molecular sciences, 2025)
This study aimed to develop and validate a dual murine model integrating a high-fat diet (HFD) and a single streptozotocin (STZ) dose to induce diabetes mellitus (DM), alongside periodontitis (Perio) induced by ligature placement and oral inoculation with Porphyromonas gingivalis (P. gingivalis). The goal was to mimic human pathological conditions, creating a physiologically relevant environment to study the interplay between DM and Perio. A total of 128 six-week-old male C57BL/6J mice were randomly divided into four groups: Control, DM, Perio, and DM-P. DM was induced by HFD and STZ injection, and Perio by ligature placement and P. gingivalis infection. Evaluations occurred at baseline and days 7, 14, and 21. Alveolar bone loss was assessed by micro-computed tomography, and inflammation was examined histologically. DM mice showed elevated glucose levels and insulin resistance. Perio and DM-P groups experienced significant bone loss compared with Control and DM groups. The morphometric analysis revealed abundant inflammatory cells and reduced collagen fibers in Perio and DM-P groups, especially at day 7. This dual murine model successfully replicated the key features of DM and Perio, maintaining overall health of the animals, and good tolerability by those subjects to the stress of both interventional procedures.